1996
DOI: 10.1182/blood.v88.5.1741.bloodjournal8851741
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the CD95 (APO-1/Fas) system in T cells from human immunodeficiency virus type-1-infected children

Abstract: Increased apoptosis of CD4+ T cells is considered to be involved in CD4+ T-cell depletion in human immunodeficiency virus type-1 (HIV-1)- infected individuals progressing toward acquired immunodeficiency syndrome (AIDS). We have recently shown that CD95 (APO-1/Fas) expression is strongly increased in T cells of HIV-1-infected children. In this report we provide further evidence for a deregulated CD95 system in AIDS. CD95 expression in HIV-1+ children is not restricted to previously activated CD45RO+ T cells bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…The increased Fas expression was found by some investigators to be in both CD4 + and CD8 + T cells 57 , 63 , 64 , 65 and, by others, to be restricted to the CD8 + T cell population 60 . T cells isolated from HIV‐infected individuals were more sensitive to Fas receptor agonist‐induced apoptosis, 57 , 61 , 63 , 64 , 66 and both the CD4 + and CD8 + subsets showed this sensitivity 57 , 63 , 64 , 66 …”
Section: The Role Of Fas/fasl In Hiv‐induced T Cell Apoptosismentioning
confidence: 98%
See 3 more Smart Citations
“…The increased Fas expression was found by some investigators to be in both CD4 + and CD8 + T cells 57 , 63 , 64 , 65 and, by others, to be restricted to the CD8 + T cell population 60 . T cells isolated from HIV‐infected individuals were more sensitive to Fas receptor agonist‐induced apoptosis, 57 , 61 , 63 , 64 , 66 and both the CD4 + and CD8 + subsets showed this sensitivity 57 , 63 , 64 , 66 …”
Section: The Role Of Fas/fasl In Hiv‐induced T Cell Apoptosismentioning
confidence: 98%
“…In addition to the observation that Fas expression is increased in lymphocytes from HIV‐infected individuals, several laboratories have reported that the expression of Fas ligand (FasL) mRNA is also increased in peripheral blood mononuclear cells 66 , 67 . However, whether this results in increased surface levels of FasL has not yet been demonstrated.…”
Section: The Role Of Fas/fasl In Hiv‐induced T Cell Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the initiation of therapy, HIV‐infected children show a substantial up‐regulation of the activation induced apoptotic marker CD95 (APO‐1) [3,4] on their T cells compared with uninfected children. It is conceivable that this contributes significantly to the pathology of the infection [5], decreasing the average life span of the child's T cells and de‐populating the peripheral pool [6,7].…”
Section: Introductionmentioning
confidence: 99%